Scope and mechanism of the highly stereoselective metal-mediated domino aldol reactions of enolates with aldehydes - Cinar, M. Emin; Engelen, Bernward; Panthöfer, Martin; Deiseroth, Hans-Jörg; Schlirf, Jens; Schmittel, Michael (Beilstein Journal of Organic Chemistry, 2016)
A one-pot transformation, which involves the reaction of ketones with aldehydes in the presence of metal halides to furnish tetrahydro-2H-pyran-2,4-diols in a highly diastereoselective manner, is investigated thoroughly by experiments and computations. The reaction was also successfully implemented on a flow micro reactor system.
Keywords: DFT; diastereoselective reaction; domino aldol; metal enolate; tetrahydropyran